2008
DOI: 10.1007/s10672-008-9065-3
|View full text |Cite
|
Sign up to set email alerts
|

Working and Caring for a Child with Chronic Illness: Challenges in Maintaining Employment

Abstract: This paper shares some pertinent findings from an initial, qualitative stage of a larger, national study currently being undertaken in Australia, exploring the support needs of parents who are working full time and caring for a child with chronic illness. The findings presented here depict the negative impact of these parents caring responsibilities on their work life and the increased stress they experience trying to maintain full time employment. In-depth interviews revealed how these parents had to rearrang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
30
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 28 publications
(39 reference statements)
4
30
0
Order By: Relevance
“…Two studies focused on detailing the challenges amongst parents of children with diverse chronic conditions that had significant and severe physical, genetic, neurological, and systemic impairments—specifically challenges/barriers in maintaining employment (George et al, ) and achieving work–family balance (George et al, ). George et al () explored and described the experiences of a sample of 12 parents working FT and caring for a child who had a chronic illness. Through in‐depth, semistructured interviews, this study illustrated that employment can have both positive and negative effects for parents.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Two studies focused on detailing the challenges amongst parents of children with diverse chronic conditions that had significant and severe physical, genetic, neurological, and systemic impairments—specifically challenges/barriers in maintaining employment (George et al, ) and achieving work–family balance (George et al, ). George et al () explored and described the experiences of a sample of 12 parents working FT and caring for a child who had a chronic illness. Through in‐depth, semistructured interviews, this study illustrated that employment can have both positive and negative effects for parents.…”
Section: Resultsmentioning
confidence: 99%
“…Yet parents reported that having flexible jobs was difficult and did not decrease stress, but rather increased frustration due to putting aside career aspirations, working unsatisfactory hours or conditions, having little access to leave entitlements, and no guarantee of work. The negative attitudes of employers, particularly their "uncaring," "inconsiderate," and "unsympathetic" approaches (George et al, 2008b) to understanding the pressures and responsibilities that they faced, added to parents' stress. George et al (2008a) also illustrate parental experiences, particularly issues faced in the workplace.…”
Section: Parent Challengesmentioning
confidence: 99%
See 1 more Smart Citation
“…Research in other contexts indicates that caring for a child with a persistent health condition creates myriad unique and difficult challenges, particularly for mothers who, across cultures, tend to function as the primary caregiver of children. These challenges include anxiety about a child's well-being, problems with maintaining employment, and a lack of social support (Burnes et al, 2008;George et al, 2008;Rini et al, 2008). It is clear that the presence of a serious health problem in a child has the potential to create distress for caregivers.…”
Section: Child Health Problems and Natural Disastersmentioning
confidence: 99%
“…This feature of family life often leads to isolation of the family from neighborhood and community just when support from a wider network would be most helpful. As more and more households require two incomes to meet modest economic standards, coping with employers becomes another challenge for families with a chronically ill child (George, Vickers, Wilkes, & Barton, , ). Challenges confronting parents include modifying work schedules, limiting working hours, and finding suitable coverage for children when a parent cannot be home.…”
Section: Literature Reviewmentioning
confidence: 99%